ABILITY OF CHILDREN TO DRAW AND SPATIALLY MODEL “A TREE” - Piwowarska, Ewa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Many well-known educationalists and psychologists noticed that children included “a tree” in their drawings very early, which usually occurred next to a figure or a building. The drawing of the tree, which was treated as a substitute of graphical picture of a figure, constituted material for the research they conducted. Artistic activity is also one of the determinants of diagnosing child’s development and one of many opportunities to say about particular topics, which are preferred by the child. Another precious activity is -next to the drawing-spatial modelling of soft material. The research conducted with the use of the technique of analysis of the artistic works aimed at defining the course of development of “a tree” drawn and spatially modelled by children at preschool age. It was important for the conducted studies to distinguish models of “a tree” – created in two art techniques – typical of particular age along with their characteristic features (clarity of the message, colouring, details used). The subject of the study concerned artworks on flat surface and three dimensional models of a tree formed by children aged 3 to 6 years. Distinguished characteristic features of the drawn and spatially modelled “tree” may become helpful for teachers in assessing development of children.